APPLICATION OF MODERN WATER-SAVING IRRIGATION TECHNOLOGIES IN CONDITIONS BUKHARA REGION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article studies water-saving irrigation technologies using polymer complexes in the conditions of old irrigated meadow-alluvial soils of the Bukhara region and their impact on the growth, development, yield of cotton and land reclamation. An analysis of the results obtained from the irrigation of saline lands in shielded containers using polymer complexes with irrigation without polymer complexes C egatami is presented.